Peranan Gaya Belajar Terhadap Prestasi Belajar Siswa Kelas IV SD Inpres 3 Tondo - Nunung Damayanti; Yusdin Bin Mahmudin Gagaramusu; Surahman Surahman; Rizal Rizal (Primary School Teacher Education Study Program; Faculty of Teacher Training and Education; Tadulako University, 2025)
Student learning styles have an influence on the learning achievements achieved by students. This research aims to describe learning styles on the learning achievements of class IV students at SD Inpres 3 Tondo. This research uses qualitative research with descriptive methods. The data collection technique used in this research is observation, interviews and documentation. Learning style is the easiest way for individuals to absorb, organize and process the information they receive. An appropriate learning style is the key to student success in learning. Visual learning style is a learning style by looking, observing, looking and the like. The strength of this learning style lies in the sense of sight. Auditory learning style is a learning style by listening. Kinesthetic learning style is a style of learning by moving, working and touching. Learning achievement is the result of measuring students which includes cognitive, affective and psychomotor factors after following the learning process which is measured using relevant test instruments. Achievement students have similar preferences, with the intensity of learning styles increasing from visual to kinesthetic, then auditory. The kinesthetic learning style occupies second place in their learning style hierarchy. Meanwhile, JE and EV show the same trend with the intensity of learning styles increasing from auditory to kinesthetic, then visual.